PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA TUNCUNG KECAMATAN MAIWA KABUPATEN ENREKANG - Suriadi Suriadi (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
This study aims to determine the community's perception of the implementation of the functions of the Village Consultative Body in Tuncung Village and to determine the various factors that encourage and hinder the implementation of these functions. The population in this study were all heads of families, amounting to 147 families. The sample was determined randomly and simply taken 5% of the total population as many as 30 families. To support the existing data, in this study 5 informants were assigned from the management of the Village Consultative Body. In this study using qualitative data analysis methods. The results of the study indicate that the community's perception of the implementation of the functions of the Village Consultative Body is known that (1) The function of establishing village regulations is not implemented. Where 53.33% of respondents stated that it was not implemented because of the lack of facilities and infrastructure to support the implementation of the function, (2) The function of accommodating and channeling the aspirations of the community was not implemented. Where 76.67% of respondents stated that it was not implemented because the community did not fully understand the functions carried out by the Village Consultative Body, so that in the process of accommodating and channeling the aspirations of the community there were often conflicts or debates from the community, (3) The implementation of the supervisory function had been carried out. Where 86.67% of respondents stated that it was implemented because it was supported by coordination and cooperation between institutions in the village. The driving factors for the implementation of the functions of the Village Consultative Body are: (1) Coordination and cooperation between institutions, 100% states that the Village Consultative Body in Tuncung Village carries out its function of carrying out good coordination with other institutions. (2) The ability and experience of community organizations that manage the Village Consultative Body, 100% states that they encourage them to carry out their functions. While the inhibiting factors are, (1) The community does not fully understand the functions carried out by the Village Consultative Body, 73.33% stated that the community lacks understanding, (2) The lack of facilities and infrastructure to support the implementation of the function, 30 respondents (100%) stated inadequate.